Evaluation of Caspase 8 Role as a Gene and Protein in Chronic Myeloid Leukemia Incidence - Mohamed, Minarose Nabeel; Altaee, Maha Fakhry (Iraqi Journal of Science, 2023)
Chronic Myeloid Leukemia )CML( is a type of clonal hematopoietic stem cell disease marked by cytogenetic abnormalities induced by the growth and division of cells carrying the Philadelphia chromosome. The current research was carried out in Iraq to examine the link between Caspase 8 gene expression and Caspase 8 protein and the development of chronic myeloid leukemia (CML) in 100 samples (50 patients and 50 controls). There were differences in the expression of this gene between healthy controls and studied patients. The relationship between CML onset with age and gender was investigated in comparison to controls. The results revealed significant rises in the mean of Caspase 8 expression level (∆Ct) of patient groups in comparison to the related ∆Ct means in the healthy group, as well as significant differences in gene expression folding (2-∆∆Ct) of Caspase 8 gene, which reached (2.778) in CML patients, Caspase 8 protein levels were (0.1059 ng/ml) and There were considerable variations between CML patients and control groups. On the other hand, the results for gender and age of CML patients compared to controls indicated no significant differences for genders of CML patients and controls, and significant differences P <0.0001 for age of CML patients and controls, this result suggests that CML may afflict people of different ages and affect both men and women.